PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP TINGKAT NYERI POST OPERASI TURP PADA PASIEN BPH DI MURNI TEGUH MEMORIAL HOSPITAL - Manullang, Elisabet Katrin; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Benign prostate Hyperplasia (BPH) is a benign tumor that often affects men and its incidence increase with age. This disease is characterized by nonmalignant groth of the prostate gland which generally occurs in men aged over 40 years. Objective: To see the effect of giving lvender aromatherapy to the level of post operative TURP pain in BPH patients at Murni Teguh Memorial Hospital. Method: This type of experimental study was pretest- posttest design using one grup design. This research was conducted in July- August 2023. The research was conducted in GB 2 and 5 South in patient room Murni Teguh Memorial Hospital. Population as sample because population is 11 patients. Univariate data to obtain frequency distribution, univariate analyis to test data normality using saphiro wilk test. The statistical test used is non- parametric, namely wilcoxon test. Result: The results of study indicate that lavender aromatherapy has an effect on reducing pain scale. Patients where the mean valur (mean) before giving lavender aromatherapy was 2.00 and the mean value after giving aromatherapy was 2,91, with a p value of 0,002 where the p value < 0,05. Conclusion: There is an effect of lavender aromatherapy on decreasing the scale pain in post operative TURP patiens.